PENGARUH DEMONSTRASI TEKNIK EVAKUASI KORBAN BENCANA TERHADAP TINGKAT PENGETAHUAN DALAM MENGHADAPI RISIKO BENCANA GEMPA BUMI - Azzahra, Khalidazia; Wulandari, Endah Tri; Azizah, Aisyah Nur (Jurnal Ilmiah Kesehatan, 2025)
Purpose: This study is to determine the effect of disaster evacuation technique demonstrations on the knowledge level of SMA Muhammadiyah Kasihan students on earthquake disaster risk management. Methods: The research employed a quantitative methodology using a one-group pre-test and post-test design. The study's population comprised of 51 students from SMA Muhammadiyah Kasihan, selected by total sampling technique. The research utilized a questionnaire regarding disaster evacuation techniques. The Wilcoxon test was employed for data analysis. Results: Before to the intervention, the demonstration of disaster evacuation techniques indicated that most respondents possessed a sufficient level of knowledge; after to the intervention, most of them demonstrated an excellent level of knowledge. The Wilcoxon test yielded a p-value of 0.000 (<0.005). Conclusion: The demonstration of disaster victim evacuation techniques affects the knowledge level of SMA Muhammadiyah Kasihan students regarding earthquakes disaster risk management.